PENERAPAN REKAM MEDIS ELEKTRONIK (RME) TERHADAP KELENGKAPAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUMAH SAKIT ANGGREK MAS - Febriyanti, Prima (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2026)
ABSTRACT Background: Electronic Medical Records (EMR) are a key component of digital transformation in healthcare services aimed at improving the quality and completeness of nursing care documentation. Complete nursing documentation supports clinical communication, quality assurance, and legal accountability in nursing practice. However, paper-based documentation systems frequently show incomplete records, particularly in the evaluation component of nursing care. Therefore, EMR implementation is expected to support more systematic and consistent documentation. Objective: This study aimed to identify the completeness of nursing care documentation before and after the implementation of Electronic Medical Records (EMR) and to analyze the impact of EMR on documentation completeness at Anggrek Mas Hospital. Methods: This study used an Evidence-Based Nursing (EBN) design with a case study approach. The sample consisted of five patient medical record files that met the inclusion criteria. Data were collected through document review using a nursing documentation audit checklist based on hospital standards. Descriptive analysis was conducted by comparing documentation completeness before and after EMR implementation. Results: Documentation completeness before EMR implementation ranged from 80–90%. After EMR implementation, completeness increased to 90–100%, particularly in nursing assessment, diagnosis, planning, and implementation. However, documentation of nursing care evaluation was not consistently recorded across all medical records. Conclusion: EMR implementation improves the completeness of nursing care documentation. However, strengthening evaluation documentation remains necessary to ensure optimal recording of all nursing process stages. Keywords: Electronic Medical Records, nursing documentation, documentation completeness, Evidence-Based Nursing, EMR.